Percepción sobre los residuos sólidos y su relación con el bienestar en pobladores del Asentamiento Humano Silfo Alván de Villa Punchana 2021 - Paredes Ocampo, Magaly (2024)
In this research work, we seek to understand the connection between the perception of solid waste and the social well-being of the residents of the AAHH Silfo Alván in the district of Punchana, Maynas, in the year 2021. The research is quantitative and uses a non-experimental design of simple relational level. The target population is residents over 18 years of age, and a sample of 113 people who met the inclusion and exclusion criteria was selected. The data collection technique used was a survey that consisted of two questionnaires of ten items each. The applied instruments passed validity and reliability tests. The collected data was analyzed and processed using the statistical package SPSS v25 and presented in a basic data matrix (MBD). The results indicate that the general perception of solid waste is unfavorable for 69.9% of residents, while only 15.9% have a favorable perception. Regarding social welfare, the majority of residents (67.3%) have a low level of social welfare. The results also indicate that there is a statistically significant relationship between the perception of solid waste and the social well-being of the residents, with a direct and high intensity association with a probability of 0.05.